An innovation technology for recovering silver and valuable metals from hazardous zinc leaching residue through direct reduction. (October 2022) - Yao, Guangzheng; Guo, Qiang; Li, Yongli; Xu, Ziyang; Han, Zhenpeng; He, Mingming; Qi, Tao
Graphical abstract: Highlights: A method for harmless utilization of zinc leaching residue is proposed. Sliver is captured by lead to FeS phase by direct reduction. Flotation with FeS as the carrier was beneficial for the recovery of the silver. The method provides ideas for recovering precious metals from hazardous waste. Abstract: Zinc leaching residue (ZLR) is a hazardous solid waste with complex phase composition, comprising high content of valuable metals, and sulfur. The extraction of silver is the key to harmless utilization of ZLR. In this paper, a short-flowsheet comprehensive recycling valuable metals method by direct reduction was proposed. During reduction, lead and zinc compounds were reduced to metallic state, which were volatilized and recovered in gas phase. Moreover, metallic iron in reduction product was recovered by magnetic separation. Silver was enriched in FeS phase, and it was beneficiated by flotation with hydrophobic FeS as carrier. Under the optimized conditions, silver concentrate with silver content and recovery of 601.43 g/t and 83.41 %, respectively; iron powder with iron content of 96.39 %; and lead and zinc volatilization rate of 78.65 % and 97.64 %, respectively, were obtained. Toxicity characteristic leaching procedure (TCLP) results indicated that tailings were harmless. The mechanisms were subsequently investigated by combining thermodynamics analyses and systematic characterizations. Especially, a one-step containing two-stage capture silver mechanism was ascertained in reduction with sulfur: formation of silver-lead alloys, and encapsulation of silver-lead alloys by FeS phase to decrease symbiotic relationship between valuable metals and slag. This entire recycling process can provide ideas for harmless recovering precious metals from hazardous waste.